På spaning efter en halvglömd genre: Litaniaminnen i ”Bön till solen” av Karin Boye - Żmuda-Trzebiatowska, Magdalena (Folia Scandinavica Posnaniensia, 2016)
The article is a presentation of partial research on litanic verse in Swedish literature carried out within the project “Litanic Verse in the Culture of European Regions”. Starting from the origins of the litanic genre, described by Witold Sadowski, the author analyses Karin Boye’s poem ”Bön till solen” („Prayer to the Sun”), paying special attention to the presence of the three litanic genes: the ektenial, the polyonymic and the chairetismic. As the typical stylistic figures and structural solutions occur in the poem, a conclusion can be drawn that ”Bön till solen” is an example of preservation of litanic patterns in the Swedish literary tradition.